FISHING GROUNDS DYNAMICS OF PURSE SEINE FISHERIES IN THE JAVA SEA - Umi Chodriyah; Eko Sri Wiyono (Indonesian Fisheries Research Journal, 2011)
Although information about fishing ground dynamics is very important to learn about the development of fishery, research on the dynamics of fishing ground is still rarely conducted. This study explains the fishing ground dynamics of purse seine in the Java Sea.